Economics of Henna in Semi-arid Rajasthan - Chand, Khem; Jangid, B L; Gajja, B L (Annals of Arid Zone, 2016)
Henna is a perennial shrub grown on a commercial scale in semi-arid Rajasthan for its dye-rich leaves. This paper provides information on the economic aspects of henna production in Pali district of Rajasthan, which is the main henna growing belt and accounts for 96% area under its plantation in the state. The analysis revealed that cost of establishing this crop in initial year was Rs. 15890 ha-1â€¢ with labor, seedlings and ploughing accounting for 55. 30 and 15% of the expenditure. respectively. Subsequently. at a recurring cost of Rs. 8464 ha-1 â€¢ the crop on an average fetched a net annual return and family labor income of Rs. 6192 and Rs. 11853. respectively. As labor accounted for major share of both establishment cost and recurring cost (about 94%), mechanization of weeding. intercultural and harvesting can further increase the profitability further. A separate regulated market for trading of dry henna leaves is functioning in Sojat city of I’ali district. Henna producers generally sell their produce in this market and get rcmunerativc prices. Dry henna leaves after processing at Sojat and Faridabad (Haryana) are marketed not only within country but exported to other countries.